Social, spatial and isotopic niche partitioning identify an estuarine community of bottlenose dolphins as a discrete management unit. Issue 12 (22nd November 2021) - Nicholson, Krista; Loneragan, Neil; Finn, Hugh; Bejder, Lars
Abstract: Investigations of population structure across multiple niche dimensions can identify discrete management units within populations. This study examined social, spatial and isotopic niche partitioning in Indo‐Pacific bottlenose dolphins ( Tursiops aduncus ) across ca. 600 km 2 of coastal and estuarine waters in south‐western Australia, to evaluate whether estuarine dolphins should be treated as a discrete management unit. Photo‐identification data and tissue samples were collected in 2016 and 2017 in a study area covering the Peel‐Harvey Estuary (PHE) and adjacent coastal waters. A total of 1, 038 dolphin groups were encountered, and 481 individuals were identified. Tissue samples for stable isotope (δ 13 C and δ 15 N) analyses were collected from 96 individuals. Social structure and complexity analyses were conducted, full and core activity spaces were identified, and their size estimated for identified social communities. Differences in stable isotope composition among individuals and communities were examined. A socially, spatially and isotopically distinct dolphin community occurred in the PHE. The coastal waters contained four socially and spatially, but not isotopically, distinct communities as well as a substantial number of dolphins ( n = 185) that were sighted infrequently and therefore were not assigned to any community. Individuals formed three levels of relationships; the majority (78%) were weak association relationships (mean half‐weight index 0.006). The estuarine community had significantly higher mean δ 13 C and significantly lower mean δ 15 N values than any of the coastal communities. There is a strong scientific basis for treating the PHE dolphin community as a discrete management unit. The estuarine and coastal communities occupied different social environments, with coastal individuals sharing space with more transient individuals. This study shows the value of integrating information from multiple niche dimensions when identifying management units, and the need to consider all encountered individuals in management planning.